Analysis of TikTok as a Research Tool in Indonesian Language and Literature Studies through Scite AI Technology - Dzil Hikma Sapitri; Hari Soedarto (Institut Agama Islam Negeri Palopo, 2025)
This study aims to explore the use of TikTok as a medium in Indonesian language and literature research through a systematic literature review (SLR), utilizing Scite AI as an analytical tool. By analyzing various studies and academic works, this research identifies emerging trends, potential benefits, and the challenges associated with using TikTok for both language learning and literary analysis. The findings highlight TikTok’s potential to be an innovative platform for enhancing language proficiency and fostering literary appreciation, offering a dynamic and interactive way for students and educators to engage with literature. However, several challenges remain, particularly regarding the validity of data obtained from TikTok content and the sustainability of long-term research efforts in this domain. These challenges include issues related to the rapid evolution of social media platforms and the reliability of user-generated content. The study concludes that, despite these challenges, TikTok has significant promise as an educational and literary tool, providing valuable insights into new ways of integrating media into language and literature studies. This research is expected to serve as a reference for scholars aiming to develop similar studies and explore the intersection of social media and academic research in the future.